Segulung Era, Sepetak Lahan - Kadek Agung Arya Krisna Kusmawa; Ida Ayu Wimba Ruspawati; I Ketut Sutapa (Pusat Penerbitan LPPM Institut Seni Indonesia Bali, 2026)
Work of Dance The 'Segulung Era, Sepetak Lahan' A Written Report and Presentation For Choreography Major Indonesian Institute of the Arts Denpasar Independent Study Program/Project 2025 By: Kadek Agung Arya Krisna Kusmawa This research focuses on the creation of a contemporary dance work titled